A diagnostic study of flood producing rainstorm of September 1988 over northwest India with the aid of a fine mesh numerical analysis system - PRASAD, K. (MAUSAM, 1992)
A numerical analysis of the synoptic situation leading to devastating floods in Punjab and adjoining states during September 1988 has been carried out. The analysis is done by three dimensional multivariate optimum interpolation (OI) scheme cast on 1° x 1° Lat./Long. Grid. Software has been developed for computation of several derived parameters and linked with the basic flow variable analysis. A diagnostic study of day-to-day rainfall versus the objectively analysed grid point fields of integrated horizontal flux divergence of water vapour is carried out, The study brings out a close spatial correspondence between the area of net moisture flux convergence on the analysis day and the area of heavy rainfall on the following day. The study suggests that the numerical analysis products can be of a good predictive value to a synoptic forecaster In heavy rainfall predictions under difficult and uncertain synoptic situations.